Stroke volume does not plateau during graded exercise in elite male distance runners - Zhou, B.; Conlee, R. K.; Jensen, R.; Fellingham, G. W.; George, J. D.; Garth Fisher, A. (Medicine & Science in Sports & Exercise, 2001)
Stroke volume (SV) responses during graded treadmill exercise were studied in 1) elite male distance runners (N = 5), 2) male university distance runners (N = 10), and 3) male untrained university students (N = 10). Methods: Cardiac output (Q) and SV were determined by a modified acetylene rebreathing procedure. Results: There were no differences in SV responses among the three groups during the transition from rest to light exercise (P > 0.05). However, the rates of change of SV during light to maximal exercise in untrained subjects (slope = -0.1544 mL.beat-1) and university distance runners (slope = 0.1041) did not change, whereas it dramatically increased (P < 0.001) in elite distant runners (slope = 0.6734). Moreover, the elite distance runners showed a further slope increase in SV when heart rate was above 160 bpm, which resulted in an average maximal SV of 187 +/- 14 mL.beat-1 compared with 145 +/- 8 and 128 +/- 14 mL.beat-1 in the university runners and untrained students, respectively (P < 0.001). Similarly, max Q reached 33.8 +/- 2.3, 26.3 +/- 1.7, and 21.3 +/- 1.5 L.min-1 in the three groups, respectively (P < 0.001). On the other hand, there was a nonsignificant tendency for maximal arteriovenous oxygen content difference to be lower in the elite athletes compared with the other groups. Conclusion: Results from university distance runners and untrained university students support the classic observation that SV plateaus at about 40% of maximal oxygen consumption despite increasing intensity of exercise. In contrast, stroke volume in the elite athletes does not plateau but increases continuously with increasing intensity of exercise over the full range of the incremental exercise test.